Dynamic Capabilities and Sustained Competitive Advantage in Indonesian Public Sector Innovation: The Moderating Role of Effectuation - Ahmad Bramantyo Nursasotyosidi; Rofiaty Rofiaty; Radityo Putro Handrito (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines how dynamic capabilities influence sustainable competitive advantage (SCA) in Indonesian public sector organizations and investigates the moderating role of effectuation. Drawing on the Dynamic Capabilities View (DCV), Resource-Based View (RBV), and effectuation logic, the study explains how sensing, seizing, and transforming capabilities sustain public sector innovation. Design/Methodology/Approach – A quantitative explanatory survey was conducted using data from 290 public service innovations selected from 1,059 KIPP Top Public Service Innovation (SINOVIK) recipients. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Findings – The results show that sensing, seizing, and transforming capabilities have positive and significant effects on SCA. Effectuation significantly strengthens these relationships, indicating that adaptive decision-making, experimentation, stakeholder commitment, and flexible resource utilization enhance the sustainability of public sector innovation. Originality/Value – This study extends the literature by integrating dynamic capabilities and effectuation to explain sustainable competitive advantage in the public sector. The findings suggest that innovation sustainability depends not only on organizational capabilities but also on adaptive decision-making, providing practical guidance for strengthening long-term public value and institutionalized service innovation.